Дорофей Бохан в межвоенной польской печати - Lavrinec, Pavel (Acta Neophilologica, 2022)
This article discusses speeches by the outstanding Russian literary figure in interwar Poland, publicist and critic Dorofey Bokhan, that appeared in the Polish press and have not yet been a subject of research. The contextual circumstances of Bokhan’s publications in Polish in the Vilnius-based socio-political and literary newspaper “Przegląd Wileński” from 1926-1927 and in the Krakow magazine of literature and art “Gazeta Literacka” from 1932-1934 are presented, supported with materials from interwar periodicals and some archival documents. The study clarifies the perceptions of the activities of Dorofey Bokhan as a Russian public figure, popularizer of Russian literature in Poland and Polish literature in Russia, a supporter of Russian-Polish rapprochement. The research materials expand knowledge concerning Russian-Polish literary and cultural connections in the period between two world wars.